PEMANFAATAN LIMBAH KONVEKSI UNTUK MENOPANG EKONOMI KELUARGA DI KELURAHAN JATI NEGARA KECAMATAN BINJAI UTARA - Yuliana, Yayuk (EDUTECH CONSULTANT, 2019)
Community service is carried out in the State Teak Village, including in the North Binjai sub-district. The land distance is approximately 4 km from the city center of Binjai. After making direct observations, in the Jati Negara Village there are several private-owned convection, such as shoe crafts and also making clothes. In this case there is convection waste in the form of convection cloth that is wasted just like that. Based on the analysis of this situation, service activities are directed towards a creative economy, namely by utilizing convection waste to be a selling value item. The service method directly conducts training in homes with informal conditions. Pamicip the material by dialogue and giving examples and showing short films of making bross hijab and piggy bank from convection waste. The results of community service are to produce piggy bank products and hijab brooches that are worth selling.